ANALYSIS OF GINGER FARMING BUSINESS IN PEAT LAND IN WEST KALIMANTAN (Case study: Ginger Farmer in Pasir Palembang Village, Mempawah Regency) - Juliana Carolina Kilmanun (Journal of Wetlands Environmental Management, 2016)
ABSTRACT Peat land potential as agricultural land in Indonesia is quite large of about 6 million hectaresout of 21 million hectares or 11% of land area in Indonesia. The utilization of peat land as agricultural land requires accurate and careful planning, appropriate technological application, and proper management because of its marginal and fragile ecosystem. Peat land has a big potential as agricultural land because this land contains high organic material. Theproblem is that the pH is very low so that it is not good for agricultural land. However, the research in Pasir Palembang Village, Mempawah Regency proved that doing ginger farming business in peat land could increase the farmers’ income and welfare. The research aims to: 1) study problems faced in doing ginger farming business, 2) know ginger farmer’s income. Data collection was done by using Focus Group Discussion method and R/C Ratio analysis. The research result found out that the main problem in ginger farming business was that of rotten tuber. Based on the analysis result it was found that R/C ratio obtained in ginger farming business was 3.4. Total revenue obtained was Rp75,000,000with the profit over cash expense was Rp53,620,000 and the profit over total expense was Rp53,470,000. Theresearch concluded that: 1) there need be a serious handling of rotten tuber disease in ginger plant, 2) doing ginger farming business could increase income and welfare of the peat land farmers in Pasir Palembang Village, Mempawah Regency.